COCONUT EMBRYO CULTURE: PRESENT STATUS AND FUTURE THRUST - M.K. Nair; Anita Karun (International Coconut Community, 1999)
The safe movement of plant genetic materials has a major concern for many countries in the world. Collecting and exchange of coconut germplasm is difficult and not economic because of the bulkiness of the seed. Moreover, due to short dormancy, the seeds germinate rapidly and thus cannot be stored for more time in a germplasm expedition. Phytosanitary restrictions too severely limit the germplasm introduction. Standardization of embryo culture technique provides an easy and safe alternative for the movement of coconut germplasm and is emphasized in the technical guidelines of FAO/IPGRI (Diekmann, 1997). In vitro culture protocols for coconut zygotic embryos have been established by various coconut research institutes in Cote d’Ivoire, France, India, the Philippines and Sri Lanka (Engelmann, 1998). An embryo culture protocol broadly consisted of at least five components, viz., field collection of embryos, in vitro active storage, in vitro retrieval, ex vitro establishment of plantlets and finally the field establishment. A detailed description of each of these components together with a comparison among different embryo culture protocols developed at various laboratories, applications made for coconut germplasm collection and development required in the future are provided here.